2012
DOI: 10.1111/j.1471-0528.2012.03484.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrosurgical bipolar vessel sealing versus conventional clamping and suturing for vaginal hysterectomy: a randomised controlled trial

Abstract: Objective To compare the effects of electrical bipolar vessel sealing and conventional suturing on postoperative pain, recovery, costs and micturition symptoms in women undergoing vaginal hysterectomy.Design Randomised controlled trial.Setting Eight teaching hospitals in the Netherlands.Population One hundred women scheduled to undergo vaginal hysterectomy for benign conditions excluding pelvic organ prolapse.Methods Women were randomised to vessel sealing or conventional surgery. The quality of life related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…In our cohort, operative time was longer in the LSJI arm as compared to the arm of the conventional method of ligation in hysterectomy (p:0.016). This result is in line with the results of Lauroy A et al and Lakeman et al 15,19 In our opinion, the longer operative time in LSJI surgeries results from the uncontrolled minor bleedings and the need for additional sutures. In other studies, on contrary, a shorter duration of operation was counted when LSJI is employed than when conventional methods were used.…”
Section: Discussionsupporting
confidence: 91%
“…In our cohort, operative time was longer in the LSJI arm as compared to the arm of the conventional method of ligation in hysterectomy (p:0.016). This result is in line with the results of Lauroy A et al and Lakeman et al 15,19 In our opinion, the longer operative time in LSJI surgeries results from the uncontrolled minor bleedings and the need for additional sutures. In other studies, on contrary, a shorter duration of operation was counted when LSJI is employed than when conventional methods were used.…”
Section: Discussionsupporting
confidence: 91%
“…Soysal et al [10] showed a linear pain score at 12 hours (3.1 ± 1.7) for both TBA and roller ball ablation, and a similar observation was made by Sesti et al [18], who reported that postoperative pain intensity at 24 hours was significantly lower in women treated with TBA than in those who underwent laparoscopic supracervical hysterectomy. Lakeman et al [21] compared the effects of electric bipolar vessel sealing and conventional suturing on postoperative pain and reported less pain on the evening after vessel sealing surgery (4.5 vs 5.7), with subsequent similar pain scores. In the present study, the conventional method of vaginal hysterectomy was used, with a postoperative pain score of 6.7 being observed on the evening of the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We read with much interest the paper by Lakeman et al ,. published in the November 2012 issue of BJOG .…”
mentioning
confidence: 98%